2011
DOI: 10.1007/978-3-642-20300-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Buser-Sarnak invariant and projective normality of abelian varieties

Abstract: Abstract. We show that a general n-dimensional polarized abelian variety (A, L) of a given polarization type and satisfying h 0 (A, L) ≥ 8 n 2 · n n n! is projectively normal. In the process, we also obtain a sharp lower bound for the volume of a purely one-dimensional complex analytic subvariety in a geodesic tubular neighborhood of a subtorus of a compact complex torus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…For p > 1 the condition is that the first p modules of syzygies among these quadrics are generated in minimal possible degree. The result of Hwang and To in [10] is essentially the case p = 0 of Theorem A.…”
Section: Our Main Results Ismentioning
confidence: 96%
See 1 more Smart Citation
“…For p > 1 the condition is that the first p modules of syzygies among these quadrics are generated in minimal possible degree. The result of Hwang and To in [10] is essentially the case p = 0 of Theorem A.…”
Section: Our Main Results Ismentioning
confidence: 96%
“…In a recent paper [10], Hwang and To observed that there is a relation between local positivity on an abelian variety A and the projective normality of suitable embeddings of A. The purpose of this note is to extend their result to higher syzygies, and to show that the language of multiplier ideals renders the computations extremely quick and transparent.…”
Section: Introductionmentioning
confidence: 88%
“…Motivated by Kollár's line of thought regarding Fujita-type conjectures, it is natural to ask whether it is feasible to study property (N p ) for a given line bundle with certain numerics instead. Such a new line of attack in the case of abelian varieties has been recently initiated by Hwang-To [HT11] where complex analytic techniques (more precisely upper bounds on volumes of tubular neighbourhoods of subtori of abelian varieties) were used to control projective normality of line bundles on abelian varieties in terms of Seshadri constants. The next step was taken by Lazarsfeld-Pareschi-Popa [LPP10], who used multiplier ideal methods to extend the results of [HT11] to higher syzygies on abelian varieties.…”
Section: Construction Of Singular Divisors and Higher Syzygies On Abe...mentioning
confidence: 99%
“…Inspired by works [HT11], [LPP11], [KL19] on (N p ) of polarized abelian varieties and a generalization of Fujita's basepoint freeness conjecture [Kol97], the author [Ito18] asks the (N p )-part of the following question. After that, both the (N p )-part and the K p,1 -part (for d 2) are stated as a conjecture by V. Lozovanu: Question 1.3 ([Ito18, Question 4.2],[Loz18, Conjecture 7.1]).…”
Section: Introductionmentioning
confidence: 99%